Cultural events as tools of developing sustainable tourism in rural areas - the case of Sevnica in Slovenia - Potočnik Topler, Jasna (Annales. Series historia et sociologia, 2021)
The purpose of this article is to identify cultural tourism as one of the best practices that can help in the implementation of the Strategy for Sustainable Growth of Slovenian Tourism (2017 - 2021) and to examine the role of cultural events as tools for the development of sustainable tourism. The latter is one of the main trends in the tourism sector, at least in the European context and also in Slovenia as a member country of the European Union. The challenge of developing sustainable tourism destinations is considerable in rural areas, where local communities must be closely observed and by all means included in the decision-making process on future tourism development. This is of the utmost importance as tourism is much more than an economic activity. Therefore, key decision-makers need to be aware that tourism activities affect all local people and many areas of their life and that the role of tourism in rural areas is to improve the quality of life of the local population. Since at least some form of culture can be found in every village, small (rural) tourist destinations often find important opportunities for sustainable tourism development in organizing cultural events, which lead to greater community visibility, cultural branding of the destination, which is significant and also several business opportunities. On the case of Sevnica, this article aims to demonstrate that there is great potential for further development of cultural tourism and its subtypes in Slovenia by further developing cultural tourism and various tourism products based on rich cultural heritage.
Keywords: cultural events; cultural tourism; kulturna dediščina; kulturne prireditve; kulturni turizem; local stakeholders; preserving heritage; Sevnica; Slovenia; Slovenija; sustainable tourism; trajnostni turizem